Research on Influence Factors of Air Quality in the Host Area of the 24th Winter Olympic Games Based on Grey Relational Analysis - Wang, Wei; Chen, Yan; Xie, Yuhan; Wu, Lifeng (Frontiers in Environmental Science, 2021)
In recent years, the continuous development of China's economy and science and technology has caused a certain degree of pollution to the atmospheric environment on which the people depend. The current air pollution problem is actively concerned by the government and all walks of life. Based on the 2015-2019 air quality indicators and some socio-economic indicators, this paper uses the grey correlation analysis method to analyze the Beijing and Zhangjiakou cities that will host the Winter Olympics in 2022. The study found that the three factors most closely related to the Beijing Air Quality Index (AQI) are the permanent population (0.831), energy consumption (0.801), the number of motor vehicles (0.79), and the permanent population (0.916) and industrial added value. (0.905), the total output value of agriculture, forestry, animal husbandry and fishery (0.89) are the three factors most closely related to the Air Quality Index (AQI) of Zhangjiakou City, and the permanent population is the common factor affecting the two cities. Considering that the factors that affect the air quality of the two cities are not exactly the same. This paper combines the development positioning of the two cities and their own characteristics, and puts forward specific suggestions and opinions on the different problems faced by the two cities. The aim is to promote the continuous improvement of air quality in the two cities to reach an excellent level through scientific and feasible air management programs before the opening of the 2022 Winter Olympic Games, and helping the 2022 Winter Olympics to be held smoothly.